THE CONTENT, FORM, METHODS AND MEANS OF EDUCATING STUDENTS IN THE SPIRIT OF INTERNATIONAL HARMONY BASED ON NATIONAL SONGS - Uspanova Rano Anuarovna (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article highlights the importance of using national songs as a means of educating students in the spirit of inter-ethnic harmony. By examining the content, form, methods, and means of integrating these cultural elements into the educational system, this study aims to demonstrate the importance of music in fostering intercultural understanding and unity among diverse student populations.